The impact of accumulated pitching counts on performance and lower body neuromuscular fatigue in baseball players: a simulated game analysis - Yeh, H.; Ho, C.; Hsieh, C.; Lau, H.; Chang, E.; Hsu, C.; Lin, W.; Ho, C. (Sports Biomechanics, 2025)
The study aimed to investigate the effects of accumulated pitching counts on lower body neuromuscular fatigue (NMF) and pitching velocity. Twelve first-level collegiate baseball pitchers completed seven simulated innings (a total of 105 pitches), during which data on ball speed, countermovement jump (CMJ), and rate of perceived exertion (RPE) were collected. Ball speed did not show a significant difference over time (F7,77 = 2.14; p = 0.57; n2 = 0.16). Except for the modified reactive strength index (mRSI) (F7,77 = 0.14, p = 0.94; n2 = 0.01), all other CMJ parameters showed significant differences (e.g. eccentric rate of force development: F7,77 = 17.44; p < 0.01; n2 = 0.53; concentric impulse: F7,77 = 9.66; p < 0.01; n2 = 0.46). RPE showed a significant difference over time (F7,77 = 52.86; p < 0.01; n2 = 0.82) with a large effect size. Accumulated pitch counts caused lower body NMF in pitchers, while ball speed remained stable. Coaches should actively monitor pitcher conditions after completing the fifth inning (75 pitches), as ball speed may not be a reliable indicator of fatigue.